2017
DOI: 10.1002/mds.27264
|View full text |Cite
|
Sign up to set email alerts
|

The iron‐deficient rat as a model of restless legs syndrome: Was anything lost in translation?

Abstract: We read with interest the article by Lai and colleagues 1 on an iron-deficient (ID) rat model for RLS, which might be promising for the discovery of novel RLS mechanisms.The diagnosis of RLS is entirely based on subjective symptoms, hindering the development of animal models.2 Appropriately therefore, Lai and colleagues 1 evaluated their model's face validity based on objective sleep derangements and periodic leg movements during sleep (PLMS), which are commonly associated to RLS. In this respect, we suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…NREM sleep is scored if an epoch consisted of ≥50% of theta or lower frequency waves as well as behavioral observation on video recordings. We do not agree with Silvani et al [2] that this is in the “twilight zone” of the wake-sleep transition. An increased EEG K-alpha complex associated with PLMs is reported in RLS patients [4].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…NREM sleep is scored if an epoch consisted of ≥50% of theta or lower frequency waves as well as behavioral observation on video recordings. We do not agree with Silvani et al [2] that this is in the “twilight zone” of the wake-sleep transition. An increased EEG K-alpha complex associated with PLMs is reported in RLS patients [4].…”
contrasting
confidence: 99%
“…Silvani et al [2] suggested some critical issues for further study in the development of animal model of RLS.…”
mentioning
confidence: 99%